Combinatorial Libraries of Biocatalysts: Application and Screening - Cipolla, Laura (Combinatorial Chemistry & High Throughput Screening, 2004)
Enzymes can perform intricate regioselective and / or enantioselective chemical transformations and can accelerate reaction rates by enormous factors all under mild conditions. However, enzymes almost always present problems for use on an industrial scale. Evolutionary design approaches can be applied to the generation of stable enzymes with improved or novel catalytic activities. Directed evolution can be considered as the biotechnological equivalent of combinatorial chemistry, where the expressed proteins are the combinatorial libraries of biocatalysts. This review will focus on the search of novel biocatalysts produced by genetic engineering with modified activity and stability in different environments, substrate specificity and enantioselectivity. Methods of screening and / or selection for the desired properties will also be described. Finally, the efforts in de novo enzyme design are mentioned.
Keywords: enantioselective